An exploration of the association between fuel subsidies and fuel riots - Neil McCulloch; Davide Natalini; Naomi Hossain; Patricia Justino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Between 2005 and 2018, 41 countries had at least one riot directly associated with popular demand for fuel. We make use of a new international dataset on fuel riots to explore the effects of fuel prices and price regimes on fuel riots. In line with prior expectations, we find that large domestic fuel price shocks-often linked to international price shocks-are a key driver of riots. In addition, we report a novel result: fuel riots are closely associated with domestic price regimes. Countries that maintain fixed price regimes-notably net energy exporters-tend to have large fuel subsidies. When such subsidies become unsustainable, domestic price adjustments are large, often leading to riots.
Keywords: 330; fuel subsidies; fuel riots; protests; conflict; price regimes; energy